Research on Simulation Analysis of Major Safety Risks and Control Countermeasures in Chemical Parks - Lujie Zhou; Rui Feng; Zhen Li; Kai Yu; Yue Li; Mingguang Zhang; Liu Pingping (Journal of Chemical Engineering of Japan)
Large chemical industrial parks are a key driver of urban economic development, characterized by significant industrialization and their proximity to urban areas. However, they also pose heightened risks related to industrial accidents and disasters. Focusing on these regions can effectively enhance safety management in urban chemical clusters. This study analyzes 222 hazardous chemical accidents, identifying 56 risk factors associated with hazardous chemicals. These factors were systematically categorized, leading to the development of safety evaluation indicators. The identified risk factors were stratified, and the weights of the evaluation indicators were calculated. Based on system dynamics theory, a dynamic risk management model for hazardous chemicals was developed through simulation. The model was applied to the Huangdao Petrochemical Zone, with initial parameters defined, followed by sensitivity analysis and iterative optimization experiments. This approach provides theoretical guidance for formulating effective control measures.